Trends in issues of the concepts of the Consejo Técnico de la Contaduría Pública as a technical accounting standardizing body in Colombia (GEON Journal (Management, Organizations and Business), 2021)
The sources of documentary information issued by standardizing bodies such as the Consejo Técnico de la Contaduría Pública (CTCP) are documents that provide the evolution and development of an institution and merit review from various research approaches; an example, are the Concepts that originate from the consultations made by natural and legal persons from both the private and public sectors. The purpose of the article is to establish the trends in the topics of the concepts issued and published by the CTCP in the period between 1992 and 2018. In this advance, the content of 6,578 concepts out of 7,191 that are published in the page of the CTCP, establishing categories related to the elements of the financial statements, the type of person making the query and the sector to which it belongs, using the frequency, tool, of descriptive statistics on the values found in the defined categories. The main conclusion is a turning point in 2009, which refers to an increase in the issuance and publication of concepts by the CTCP possibly due to the change in the accounting model in Colombia for that same year; the contribution of the article is an advance and proposal to work with documentary sources issued by public institutions of the profession, in this case with a descriptive approach, but which can be covered from other research approaches and methodologies.
Keywords: M41 Accounting; M48 Government Policy and Regulation; Accounting; Concept; GESTIO; Normalizing body; Trend